Quantitative Analysis of Factors Affecting the Realization of Smart Government in Iran with Emphasis on the Dimensions of Digital Governance - Fathi, Babak; Rahimi, Gholamreza; Nejhad Haji Ali Irani, Farhad (Digital Transformation and Administration Innovation, 2025)
This study aims to quantitatively examine the factors affecting the realization of smart government in Iran with an emphasis on the dimensions of digital governance. The research employed a descriptive-correlational survey design and targeted experts and managers in the field of information technology and digital transformation in Iran’s public sector. A structured questionnaire was used to collect data from a sample of 384 participants selected via purposive sampling. The instrument measured constructs such as IT infrastructure, digital governance, organizational agility, digital policymaking, and citizen participation. Data analysis was conducted using SPSS and AMOS software. Structural Equation Modeling (SEM) was employed to test hypothesized relationships and evaluate the measurement and structural models. Inferential statistical analysis using SEM confirmed that all hypothesized relationships were statistically significant at p < 0.001. IT infrastructure (β = 0.804, t = 9.653), comprehensive service delivery (β = 0.308, t = 7.118), choice provision (β = 0.760, t = 9.35), security (β = 0.809, t = 9.39), goal alignment (β = 0.654, t = 12.34), smart services (β = 0.756, t = 7.118), and other factors such as digital governance, digital roadmaps, and smart interaction showed significant positive effects on the realization of smart government. Digital policymaking and digital governance emerged as the strongest predictors. The model’s goodness-of-fit index (GOF = 0.56) indicated a strong overall model fit. The coefficient of determination (R²) for the final structural model was 0.72, demonstrating high explanatory power. The realization of smart government in Iran is significantly influenced by a combination of digital infrastructure, governance mechanisms, policymaking strategies, organizational agility, and civic engagement. Among these, strategic digital policymaking and robust digital governance play pivotal roles. These findings underscore the need for integrated digital strategies and institutional capacity building to support the digital transformation of public administration in Iran.